PENGARUH DIVERSITAS GENDER DALAM DUA DEWAN TERHADAP PENGUNGKAPAN ESG PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Amelia Natafa; Siti Mutmainah (Diponegoro Journal of Accounting, 2025)
This study was conducted to analyze the influence of gender diversity within a two-tier board system (board of directors and board of commissioners) as a governance mechanism to reduce information asymmetry between management (agent) and shareholders (principal) through Environmental, Social, and Governance (ESG) disclosure. The study was conducted on consumer manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Gender diversity on the board of directors and board of commissioners was measured using the proportion of women, with firm size as a control variable.The dependent variable in this research is ESG disclosure, which was measured using the composite ESG disclosure score as well as individual pillar scores (Environmental, Social, and Governance) sourced from the Bloomberg database. This research utilizes secondary data from annual and sustainability reports. The sample was selected using a purposive sampling technique based on data availability, resulting in a total of 129 observations.The results indicate that gender diversity on the board of directors has a significant positive effect on the level of composite ESG disclosure, particularly on the environmental and social pillars. Similar findings were also demonstrated by gender diversity on the board of commissioners. From the perspective of agency theory, this finding indicates that a more diverse board is able to enhance its monitoring function, thereby encouraging management (agent) to be more transparent in reporting the management of non-financial risks for the benefit of shareholders (principal). However, this study did not find a significant influence of gender diversity on either board on the disclosure of the governance pillar.